Prophet Ibrahim's Search for Allah - Khan, Saniyasnain (Ajman,U.A.E Iqra book Distribution, 2024)
This enchantingly illustrated board book, delightfully introduces to the children the inspiring story of the Prophet Ibrahim.
Keywords: Islamic Book